THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING METHOD IN TEACHING SPEAKING - Bandung, Murti (Proceedings Education and Language International Conference, 2017)
The background of the study in this research is based on the researcher’s experience when doing teaching practice, in which method used by the teacher in teaching and learning process was often assumed as the factor that cause the students speaking problem. So, the researcher used another method in this case the method of contextual teaching and learning can develop the students’ ability in English speaking skill. The design of this research is an experimental study. The kind of the data collected is quantitative data. The data were analyzed statistically by using homogeneity test and t-test. Data analysis was from the beginning and the ending of experimental and control class that is taken from test where as pre and post test score. In addition, homogeneity test and t-test used to prove the hypothesis that has been planned before. There are difference score between students taught using CTL method and conventional method. It is shown that the average of experimental class is higher than control class 78.24 > 73.23. Besides that, the test of hypothesis using t-test shown the result is higher than the number of the t-table. The result of t-test is 33.4 and the number of t-table on α = 5% is 1.98 (33.4>1.98). The hypothesis (Ha) is accepted. Keywords: speaking, contextual, CTL method.